Atopic dermatitis-like superficial morphea. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Superficial morphea is a variant of scleroderma characterized mainly by discolored patches that symmetrically affect the folds (1). These patches are not associated with erythema, they are not sclerotic at all and are never complicated by contractures; there may be minimal atrophy as in our case (2). Superficial morphea clearly prevails in the female sex, as only one case has been described in a male (1). It must be differentiated from idiopathic atrophoderma of Pasini-Pierini from which it differs for the lack of the peripheral depression known as sign of the cliff, and from lichen sclerosus, which is not hyperpigmented, usually affects the genital mucous membranes and presents small lichen papules in the periphery. The current case is characterized by the presence of itching. The latter, together with the symmetrical involvement of the folds, was reminiscent of atopic dermatitis.